IMPORTANCE OF INTOATION IN ENGLISH - Teshaboyeva Nafisa Zubaydulla qizi; Ne`matova Marjona G`ayrat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The purpose and significance of intonation in spoken language are examined in this article, with an emphasis on its meaning. The changes in pitch that occur during speech to express emotional tone, distinguish between different sentence forms, highlight important words, and aid in discourse organization are referred to as intonation. It is an essential component of prosody, which encompasses speech stress and rhythm. The article emphasizes the role intonation plays in expressing emotion, elucidating sentence structure (e.g., separating statements from questions), and indicating concentration or emphasis in discourse. It also highlights the role of intonation in pragmatics, where tone reflects social intentions, politeness, and speaker relationships; it also discusses how intonation contributes to the meaning of speech in various contexts and cultures, pointing out that changes in pitch can change how a sentence is interpreted; and, through the analysis, it shows that intonation is not just a vocal feature but a crucial tool in comprehending and forming communication.